Perception of illness and disease, an overview of a diet of people with type 2 diabetes in the COVID-19 era - Nastaina, Hayu Iyaka; Padmawati, Retna Siwi; Purba, Martalena Br (BKM Public Health and Community Medicine, 2022)
Purpose: One of the management of diabetes mellitus is diet needs special attention, mainly when the pandemic occurred in 2020, which more or less affected people with diabetes in accessing health services. This study aimed to provide an overview of the understanding of type 2 diabetes mellitus and dietary patterns in people with type 2 diabetes (T2DM) with COVID-19. Methods: This is qualitative research with a case study approach. Researchers collected data through in-depth interviews and observations. The case study was conducted in 2 areas of Kampung Tangguh in Malang, a populated village with a lower-middle economic level. Selection of research participants using a purposive sampling method. In this study, a total of 14 participants were diagnosed with diabetes with an age limit of 45-71 years. Results: People with T2DM view diabetes as a disease that must be managed well in terms of medication and diet. The significant role of others, such as family, cadres, and health workers, is needed to support successful diabetes management. Kampung Tangguh, with its health dimension, has not been able to play a role in health resilience in the community. The diet applied is still not adequate. Socio-economic is one of the influencing factors. Conclusions: People with T2DM must anticipate themselves to manage DM and improve their quality of life successfully. The dimension of health resilience in Kampung Tangguh needs to be maximized with the role of cadres as a preventive effort against degenerative diseases in the community.